Flow dynamics and structure of solid pellets along the channel of a single screw extruder - Michelangelli, O. P. (2011)
Plasticating single screw extrusion involves the progressive compaction and heating of loose solid pellets that eventually melt, form a relatively homogenous stream and are subsequently pumped through a shaping tool. Traditional analyses of the solids conveying stage assume the sliding of an elastic solid plug due to differential wall friction coefficients. However, not only the corresponding predictions may fail considerably, but it is also well known that, at least in the initial screw turns, pellets are far from compact. This work follows previous efforts to model the flow of solids in the hopper and initial screw turns using the Discrete Element Method (DEM). The model considers the development of normal and tangential forces resulting from the inelastic collisions between the pellets and between them and the neighbouring metallic surfaces. As an example of the capability of the model to capture detailed features of granular flow, the effect of pellet size on flow is discussed.